Hepatocellular carcinoma with intracranial metastasis in a Japanese macaque (Macaca fuscata). Issue 3 (3rd April 2017) - Miyabe‐Nishiwaki, Takako; Hirata, Akihiro; Kaneko, Akihisa; Ishigami, Akiyo; Miyamoto, Yoko; Yamanaka, Atsushi; Owaki, Keishi; Sakai, Hiroki; Yanai, Tokuma; Suzuki, Juri
Abstract: Background: A 23‐year‐old male Japanese macaque ( Macaca fuscata ) showed left ptosis, which progressed to exophthalmos. Methods: The macaque underwent a clinical examination, CT and MRI, and was euthanized. Necropsy and histopathological examination were performed after euthanasia. Results: The CT revealed and MRI confirmed an intracranial mass at the skull base with orbital extension. At necropsy, there were a large hepatic mass and an intracranial mass compressing the left temporal lobe of the brain. Histopathological and immunohistological examinations revealed that the masses were hepatocellular carcinoma (HCC) and a metastatic lesion. In both the primary and metastatic lesions, neoplastic hepatocytes were arranged mainly in a trabecular pattern. Immunohistochemically, the tumor cells were positive for cytokeratin (AE1/AE3 and CAM5.2) and hepatocyte paraffin 1 and negative for cytokeratin 7 and 20 and vimentin. Conclusion: To our knowledge, this is the first case report of HCC with intracranial metastasis in a macaque.